The structure of b-diketones related to curcumin determined by X-ray crystallography, NMR (solution and solid state) and theoretical calculations - Nieto, Carla I. (2016)
Structural data are reported in sixteen ketoenols of beta diketones, solution NMR, solid-state NMR (CPMAS and MAS) and X-ray crystallography (four compounds, where three are new). The emphasis is on the tautomerist between both ketoenols, both in solution and solid-state. GIAO-B3LYP 6-311g (d,p) and Quantum ESPRESSO (QE) calculations were used and compared. For average values, the GIAO-DMSO-PCM is enough but splittings can only be approached by using QE. A case of rotational disorder has been analyzed. Some anomalies related to C-F bonds and to the C-CF3 group have been detected.